Trends in traumatic out-of-hospital cardiac arrest in Perth, Western Australia from 1997 to 2014 - Beck, B.; Tohira, Hideo; Bray, J.; Straney, L.; Brown, E.; Inoue, M.; Williams, Teresa; McKenzie, N.; Celenza, A.; Bailey, P.; Finn, J. (2015)
Aim: This study aims to describe and compare traumatic and medical out-of-hospital cardiac arrest (OHCA) occurring in Perth, Western Australia, between 1997 and 2014. Methods: The St John Ambulance Western Australia (SJA-WA) OHCA Database was used to identify all adult (≥16 years) cases. We calculated annual crude and age-sex standardised incidence rates (ASIRs) for traumatic and medical OHCA and investigated trends over time. Results: Over the study period, SJA-WA attended 1,354 traumatic OHCA and 16,076 medical OHCA cases. The mean annual crude incidence rate of traumatic OHCA in adults attended by SJA-WA was 6.0 per 100,000 (73.9 per 100,000 for medical cases), with the majority resulting from motor vehicle collisions (56.7%). We noted no change to either incidence or mechanism of injury over the study period (p > 0.05). Compared to medical OHCA, traumatic OHCA cases were less likely to receive bystander cardiopulmonary resuscitation (CPR) (20.4% vs. 24.5%, p = 0.001) or have resuscitation commenced by paramedics (38.9% vs. 44.8%, p < 0.001). However, rates of bystander CPR and resuscitation commenced by paramedics increased significantly over time in traumatic OHCA (p < 0.001). In cases where resuscitation was commenced by paramedics there was no difference in the proportion who died at the scene (37.2% traumatic vs. 34.3% medical, p = 0.17), however, fewer traumatic OHCAs survived to hospital discharge (1.7% vs. 8.7%, p < 0.001). Conclusions: Despite temporal increases in rates of bystander CPR and paramedic resuscitation, traumatic OHCA survival remains poor with only nine patients surviving from traumatic OHCA over the 18-year period.